Nature, raison et nation dans le modernisme shï'ite de l'Inde britannique - Michel Boivin (Revue des Mondes Musulmans et de la Méditerranée)
In South Asia, as in the rest of the Muslim world, colonial domination gave rise to many questions for Muslims. By trying to understand why they were dominated, they went on to build an aggiornamento. If the ideas of thinkers like Sayyid Ahmad Khân (1817-1898) has been well studied, the role played by Shfites such as Sayyid Amîr'Alî (1849-1928), an Ithnâ 'Asharî Shî'ite, or Sultan Muhammad Shah Aghâ Khân (1877-1957), an Ismâ'ilî Shî'ite, is little known. For these authors, who often gave rebuttals to Christian polemists, the Quranic message was divided into two fundamental features: the « eternal » verses, those related to the fundamentals of the faith, and the « temporary » verses, those related to pragmatic problems which occurred during the Prophet's lifetime. By making this distinction, they gave birth to a liberal and secularist conception of Islam which shaped an Islamic rationalism. On the political level, even if they were activists in the first Muslim associations, they were not able to envision the concept of a Muslim Nation in India although Sultân Muhammad Shâb Aghâ Khân acclaimed the birth of Pakistan.